2004
DOI: 10.1021/ac034869m
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High-Efficiency Strong Cation Exchange LC/RPLC/MS/MS for High Dynamic Range Characterization of the Human Plasma Proteome

Abstract: High-efficiency nanoscale reversed-phase liquid chromatography (chromatographic peak capacities of approximately 1000: Shen, Y.; Zhao, R.; Berger, S. J.; Anderson, G. A.; Rodriguez, N.; Smith, R. D. Anal. Chem. 2002, 74, 4235. Shen, Y.; Moore, R. J.; Zhao, R.; Blonder, J.; Auberry, D. L.; Masselon, C.; Pasa-Tolic, L.; Hixson, K. K.; Auberry, K. J.; Smith, R. D. Anal. Chem. 2003, 75, 3596.) and strong cation exchange LC was used to obtain ultra-high-efficiency separations (combined chromatographic peak capaciti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
262
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(270 citation statements)
references
References 29 publications
6
262
1
1
Order By: Relevance
“…Presently, the largest databases of identified proteins from either human serum or plasma contain between approximately 1450 [18] to 1700 proteins [19]. The proteins in these studies, however, were identified from searching MS/MS spectra in which multiple different enzyme constraints were allowed and many of the proteins were identified by a single peptide.…”
Section: Resultsmentioning
confidence: 99%
“…Presently, the largest databases of identified proteins from either human serum or plasma contain between approximately 1450 [18] to 1700 proteins [19]. The proteins in these studies, however, were identified from searching MS/MS spectra in which multiple different enzyme constraints were allowed and many of the proteins were identified by a single peptide.…”
Section: Resultsmentioning
confidence: 99%
“…35 Although reported peak capacities are not absolute indices and thus are hard to compare, this is undoubtedly an important achievement because improved RP separation has a direct impact on the total system performance of multidimensional methods. 36,37 Commercially available UPLC systems and mass spectrometers capable of taking advantage of the narrower peak widths have engendered increased interest in this technology for proteomics applications.…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…Immunohistochemistry can distinguish about 300, gel electrophoresis almost 500, and mass spectrometry 800-1000 serum proteins. 30 Since the occurrence of the different proteins is not the same, if we first remove the ones that are present in highest quantity and then condense the rest, the number of distinct proteins (and peptides) reaches about 3,700. However, the examination of the amino acid structure has revealed that these are not all distinct molecules: more than one third of them are the results of post-translational (epigenetic) modifications.…”
Section: The Proteome Of the Human Serum And Its Examinationmentioning
confidence: 99%